Experimental image and range scanner datasets fusion in SHM for displacement detection - Rivera-Castillo, Javier; Flores-Fuentes, Wendy; Rivas-Lopez, Moisés; Sergiyenko, Oleg; González-Navarro, Félix F.; Rodríguez Quiñonez, Julio C.; Hernández-Balbuena, Daniel; Lindner, Lars; Básaca-Preciado, Luis C. (My University, 2016)
Optical images and signals can be used to detect displacement in civil engineering structures. This paper presents a technical experimentation of a vision‐based technology and artificial intelligence algorithms methodology for structural health monitoring of new and aging structures, by a noncontact and nondestructive system. The experimental study emphasis is on the outdoor urban environment, by the detection of spatial coordinate displacement on the structures, in order to perform a damage assessment. Also, the experimental study contains both theoretical and experimental aspects of the fusion of image and range scanner datasets created using intelligent algorithms. A camera and an optical scanning system were used to generate high resolution and quality images for 2D imaging, and 3D accuracy range data from optoelectronic sensor signals. Scans at a specific area of an engineering structure were performed to measure spatial coordinates displacements, successfully verifying the effectiveness and the robustness of the proposed non‐contact and nondestructive monitoring approach.
Structural Control and Health Monitoring
Keywords: Artificial intelligence tools; Data acquisition; Health monitoring; Measurements; Sensors for damage detection; Signal processing